Digital volume / Satriarahman Ghazali and Suhaimi Sulaiman - Ghazali, Satriarahman; Sulaiman, Suhaimi (2003)
Project 2 (KEU 380) is a subject that must be taken by the student while in semester 6 of Diploma in Electrical Engineering. This subject has 3 credits hour-non-core. The project needs 2 members for each group. For our project, the name is ‘Digital volume’. The function of this project is to display the numerical number (0 to 9) using the 7-LED segment display. The number can be adjusting by rotating the rotary encoder. In this thesis, this project can be combine to other application such as controlling circuit, selector circuit, and in dialing the phone number. Here we have make for the output of this circuit to be connected with another circuits. The proposed project will provide a more reliable and more precession when the range of displaying numerical number is added to higher digit. The generated clock will be change from its own created by rotary encoder to a continuous signal with the IC timer (555).